The 3-D extinction law in the 2nd quadrant of the Galactic disk. Issue Volume 9:Issue S298(2013) (6th January 2014) - Liu, Chao; Fang, Min; Wu, Yue; Carrell, Kenneth; Xue, Xiangxiang; van de Ven, Glenn
Abstract: We estimate the 3D extinction law in the optical–NIR bands for a line of sight in the 2nd quadrant of the Galactic disk. Two dust lanes are identified at 9 and 10.25 kpc in both A V and R V, indicating that the size of the dust grains in the spiral arms is larger than that in the inter-arm regions.